Bacterial Contamination Test on Smoked Baung Fish for Sale in Tenggarong District in 2022 - Fifi Mufiana Nurrahma; I Gede Andika Sukarya; Maria Eka Suryani (Formosa Journal of Science and Technology, 2023)
Fish is a food source that contains nutrients such as protein which is very good for public consumption, but fish quickly experience a process of decay. To prevent this, a preservation process is carried out, for example by the smoking method. The purpose of this study was to determine the Total Plate Count (TPC) of smoked baung fish sold in Tenggarong District according to the standards set by SNI 2725: 2013, which cannot be > 5 x 104 CFU/g. This type of research is descriptive. The research sample is 5 smoked baung fish sold by traders in Tenggarong District and the sampling technique is total sampling. All samples were examined in duplicate. The analysis technique of this research is univariate. The results of the study of 5 samples of smoked baung fish, obtained an average TPC value of 2.4 × 104 in all samples, which means they still meet the SNI requirements.